Compositional partitioning during early stages of oxidation of a uranium-molybdenum alloy. (15th April 2022) - Kautz, Elizabeth J.; Lambeets, Sten V.; Royer, Jacqueline; Perea, Daniel E.; Harilal, Sivanandan S.; Devaraj, Arun
Graphical abstract: Abstract: Compositional partitioning during uranium alloy oxidation was studied via complementary ex situ - in situ atom probe tomography. Nanoscopic volumes of uranium- 22 at. % molybdenum were exposed to air at room temperature/atmospheric pressure for 30–60 minutes (ex situ), and 300  ∘ C - 10 − 5 mbar O 2 gas for 2–5 minutes in a chemical reaction chamber attached to an atom probe system (in situ). For all environmental conditions, a hypostoichiometric uranium oxide is formed. Reaction fronts are observed at oxide/metal, oxide/hydride, and outer oxide/environment interfaces. Results reveal Mo redistributes across the oxide/metal interface, with a tendency for enrichment in the outer oxide. The formation of a hydrogen-rich subsurface layer between the oxide and base alloy accompanies oxidation in both air and oxygen gas environments. Carbon and silicon impurity elements also redistribute to the outer oxide, contributing to oxide film composition.